Peran Guru Dalam Menghadapi Anak Hiperaktif Pada Siswa Kelas Rendah Di SD Negeri Jruek Kabupaten Aceh Besar - Mughni Alya (Universitas Syiah Kuala, 2023)
The teacher's role is very important in teaching and learning activities, the teacher does not only serve as a motivator and inspiration but also helps accompany and guide hyperactive children. Based on the formulation of the problem, the researcher wants to know, what is the teacher's role in dealing with hyperactive children in low grade students at Jruek Public Elementary School, Aceh Besar District. This study used a qualitative approach with a descriptive research type. The subjects in this study were 3 students and 2 class teachers at Jruek Public Elementary School, Aceh Besar District. The techniques used in data collection are observation and interviews. Data were analyzed using data reduction, data collection and conclusion. Based on the results of research at Jruek Public Elementary School, Aceh Besar District, the teacher's role in dealing with hyperactive children can be said to be quite good. This can be seen from the efforts of teachers in carrying out their role in dealing with hyperactive children. As for some of the teacher's roles, namely as a good source of information, as a motivator who can motivate children's learning enthusiasm, as a facilitator who can adjust to children's needs, as a good guide in guiding children through approaches and giving additional classes, as a demonstrator who can convey learning material well, as a class manager who can control the classroom atmosphere to be conducive, as a mediator who can provide learning media and as an evaluator who evaluates hyperactive children.